David Busch's Canon EOS R6 II guide to digital photography - Busch, David D. (Rocky Nook, 2023)
David Busch's Canon EOS R6 II Guide to Digital Photography is your all-in-one comprehensive resource and reference for the exciting new Canon EOS R6 II full-frame mirrorless camera. The EOS R6 II boasts continuous shooting up to 40 frames per second, in-body image stabilization, and a 24 MP sensor. Its upgraded autofocus subject recognition now provides lightning-fast tracking of people, animals, motor sports vehicles, aircraft, and trains. Three available adapters make it easy to supplement your R-mount lenses with a broad selection of legacy Canon EF and EF-S optics. The EOS R6 II has wireless connectivity to allow linking the camera to a computer and iOS or Android smart devices, high-definition 4K and Full HD movie-making capabilities, and a versatile swiveling touch screen LCD. With this book in hand, you can quickly apply all these advanced features to your digital photography, while boosting your creativity to take great photographs with your Canon EOS R6 II. Filled with detailed how-to steps and full-color illustrations, David Busch's Canon EOS R6 II Guide to Digital Photography covers all this upscale camera's features in depth, from taking your first photos through advanced details of setup, exposure, lens selection, lighting, and more, and relates each feature to specific photographic techniques and situations. Also included is the handy EOS R6 II "roadmap" chapter, an easy-to-use visual guide to the camera's features and controls. Learn when to use each option and, more importantly, when not to use them, by following the author’s recommended settings for every menu entry. With best-selling photographer and mentor David Busch as your guide, you'll quickly have full creative mastery of your camera’s capabilities, whether you're shooting on the job, as an advanced enthusiast, or are just out for fun. Start building your knowledge and confidence, while bringing your vision to light with the Canon EOS R6 II today.